The BE + -ING form: Progressive aspect and metonymy - Grégory Furmaniak (Corela)
We propose a unitary analysis of the English Progressive Present. Difficult as it may be to account for some of its uses in aspectual terms alone, we argue that referring to an event in progress at a given moment is the main function of the BE + –ING form. Yet, this meaning does not emerge out of the blue. It is a semantic construct resulting from a complex cognitive process. Our contention is that this underlying thought process (based on metonymy) can, in certain circumstances, take over the aspectual meaning without, however, deleting it completely.